Pemanfaatan Web Design untuk Meningkatkan Pemasaran UMKM Ayam Pecak 99 dengan Blogger di Kota Padang - Siska Mariyanti; Silva Febria Yutrisna; Novadilastri Novadilastri; Sularno sularno (CV. ITTC INDONESIA, 2025)
The rapid development of information technology requires micro, small, and medium enterprises (MSMEs) to adapt to more effective digital marketing strategies. This study aims to examine the utilization of web design through the Blogger platform as a promotional tool to improve the marketing performance of Ayam Pecak 99 MSME in Padang City. The research uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. The results show that the implementation of an attractive, informative, and user-friendly web design increases business visibility on search engines and expands consumer reach. Furthermore, consistent digital content on Blogger helps build brand image and customer trust. Therefore, the use of Blogger-based web design serves as a strategic alternative for MSMEs to enhance digital marketing and competitiveness in the era of technological transformation.